EXAMINING THE PATTANI CENTRAL MOSQUE AMID THE SOUTHERN THAILAND CONFLICT - Ridwan Ridwan (Jurnal Kajian Wilayah, 2015)
Generally speaking, mosques and pondok (Islamic boarding schools) in Southern Thailand are regarded as place for fostering Muslim militants. In Pattani, many mosques are taken for granted as places to recruit Muslim militants against the Thai Government. For instance, Kru-Ze Mosque incident in 2004 had raised various militant, Islamist activities against the central government. In this regard, I believe that Pattani Central Mosque has non-violenceelements that could be activated as a sanctuary to hinder the unjust violence. Therefore, this article will examine the real quality of Pattani Central Mosque in southern Thailand on the basis of its profile. Consequently, readers would grasp a general picture about those matters. Thus, by analyzing the religious practices within the mosque,I conclude that Pattani Central Mosque seems to be composed of a fairly equal mixture of moderate and more conservative Muslims instead of those with radical and extreme tendencies.Keywords: Mosque, Islamic teaching practices, Salafy-Wahaby